PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN REMBANG - Anengtyas Puspita Nur Hasanah; Dian Ayu Liana Dewi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The purpose of this study is to identify and demonstrate the influence of leadership, working conditions, and motivation on employee performance. This study used a sample of 41 DINDUKCAPIL employees in Rembang Regency, using a saturated sampling method, so that all existing employees became research subjects. To analyze the data, reliability tests, validity tests, t-tests (partial), and coefficient of determination (R²) analysis were used, processed using the latest version of SPSS. The results showed that leadership has a positive, although not significant, influence on employee performance. The same is true for the working conditions variable, which shows a positive but not significant impact. In contrast to the two previous variables, motivation shows a statistically significant positive influence on employee performance. The results of the coefficient of determination (R²) analysis obtained a value of 0.497, which means that 49.7% of the influence of leadership, working conditions, and motivation on employee performance. Meanwhile, the remaining 50.3% is influenced by other independent variables not included in this study.